fillm realita imaji - Muhlisiun, Arda (Institut Seni Indonesia Padangpanjang, 2023)
In visual arts, particularly in film, the relationship between reality and imagination creates a complex relation. Film, as a medium that amalgamates visual techniques, special effects, and cinematic direction, possesses the power to construct a highly realistic world. This enables the audience to experience emotional engagement with visuals, characters, and the narrative. This research aims to address the question: how does film establish engagement between reality and imagination? The proposed hypothesis is that the cinematic power and its creative elements generate a convincing representation of the world for the audience's perception, blurring the boundaries between reality and fantasy. The research methodology employs a narrative transportation approach and refers to a range of literature to highlight the intricacies of reality in film, where the emotional and cognitive involvement of the audience is crucial for a profound cinematic experience. This study seeks to provide an understanding of how films create complex relationships between images and reality. In conclusion, films not only produce visual images but also shape alternative realities that influence the perception and even behavior of the audience. Therefore, critical discussion of the boundaries between reality and imagination in films is very important).